Pemanfaatan Citrus aurantifolia (Christm. et Panz.) sebagai Bahan Pangan dan Obat serta Bioaktivitas - Marina Silalahi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Lime or Citrus aurintifolia (CA) is a type of medicinal plant that has long been used by local communities in Indonesia. Besides being used as traditional medicine, the fruit is also used for a variety of food or drinks. The use of plants as traditional medicine is related to the bioactivity and content of secondary metabolites. This study aims to explain the relationship between the use of CA as traditional medicine and its bioactivity. The method used is a literature review published online on Google Scholar and also scientific journals about CA using CA keywords, CA uses, and CA biaoctivities, then synthesized so as to obtain comprehensive information. In ethnobotany CA is used to treat fever, sauna ingredients, cough medicines, to increase stamina, overcome hypertension, and anti-cholesterol. Various researchers have successfully demonstrated the bioactivity of CAs which are anticholesterol, antimicrobial, antioxidant, antihypertension, antiosteoporosis and anticancer. Essential oils found in the leaves and fruit are compounds responsible for their bioactivity. The ability of CA as an antimicrobial can be very potential to be developed for health as well as a natural food preservative.